The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1128/msystems.00056-21
|View full text |Cite
|
Sign up to set email alerts
|

Case-Control Microbiome Study of Chronic Otitis Media with Effusion in Children Points at Streptococcus salivarius as a Pathobiont-Inhibiting Species

Abstract: Chronic otitis media with effusion (OME) has been associated with a shift in microbiome composition and microbial interaction in the upper respiratory tract (URT). While most studies have focused on potential pathogens, this study aimed to find bacteria that could be protective against OME through a case-control microbiome study and characterization of isolates from healthy subjects. The URT and ear microbiome profiles of 70 chronic OME patients and 53 controls were compared by 16S rRNA amplicon sequencing. Ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 96 publications
2
18
0
2
Order By: Relevance
“…Most of the samples analyzed are from OME cases (85.71%). Therefore, the identification of H. influenzae as the most prevalent pathogen in the MEF agrees with other studies that report H. influenzae as the predominant pathogen in OME [8,14,35]. However, the reported prevalence rates are highly variable due to different health care programs, particularly vaccination, in various geographical locations [36].…”
Section: Discussionsupporting
confidence: 89%
“…Most of the samples analyzed are from OME cases (85.71%). Therefore, the identification of H. influenzae as the most prevalent pathogen in the MEF agrees with other studies that report H. influenzae as the predominant pathogen in OME [8,14,35]. However, the reported prevalence rates are highly variable due to different health care programs, particularly vaccination, in various geographical locations [36].…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, probiotic treatment with Streptococcus salivarius has been explored for children suffering from chronic otitis media. S. salivarius can inhibit growth of most pathogens known to cause otitis media infections, among others including S. pneumoniae, H. influenzae, M. catarrhalis [37,38]. However, it has not yet been shown that D. pigrum supplementation, in isolation or combined with Corynebacterium, can also effectuate short-term or long-term clinical improvement.…”
Section: Resultsmentioning
confidence: 99%
“…Corynebacterium is also commonly identified in COM but is typically viewed as a commensal, even potentially otoprotective in acute OM ( Lappan et al., 2018 ; Jorissen et al., 2021 ). In contrast, Porphyromonas , Fusobacterium and Campylobacter ( Figure 1 , Figure 3 ) are less commonly isolated from patients with COM or cholesteatoma ( Brook, 1995 ; Yusuf et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%